Teaching two children with autism spectrum disorder to use a speech-generating device. Issue 1 (2nd January 2018) - Sigafoos, Jeff; Roche, Laura; Stevens, Michelle; Waddington, Hannah; Carnett, Amarie; van der Meer, Larah; O'Reilly, Mark F.; Lancioni, Giulio E.; Schlosser, Ralf W.; Marschik, Peter B.
ABSTRACT: Many children with autism spectrum disorder have minimal speech and are therefore candidates for learning to use speech-generating devices. Previous research has mainly focused on teaching children to use speech-generating devices to request preferred objects. While this is an important communication function, it would seem equally important for children to learn other communication functions, such as learning to reject non-preferred objects and learning to request breaks from non-preferred activities. The purpose of the present study was to evaluate procedures for teaching two children with autism spectrum disorder to use speech-generating devices for these different communication functions. The first child was taught to request preferred foods and reject non-preferred foods. The second child was taught to request a preferred toy and request a break from learning activities. Intervention involved creating opportunities for communication and then applying time delay, graduated guidance, and contingent reinforcement procedures. With intervention, both children learned to use the speech-generating device to perform their two respective communication responses. The results suggest a promising approach for teaching multifunction use of speech-generating devices to children with autism spectrum disorder.